1999
DOI: 10.1029/1999gc000013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the presence of garnet‐pyroxenite in the mantle sources of basalts through combined hafnium‐neodymium‐thorium isotope systematics

Abstract: [1] The existence of an enriched component in the mantle with a pyroxenitic or eclogitic composition and its importance for basalt genesis has been discussed for over two decades. Inferences about the depth of melting as well as the dynamics of melting based on the presence of garnet and the location of the spinelgarnet transition are different if garnet-pyroxenite is present in the peridotitic mantle. Trace element partition coefficients are dependent on composition, and the differences between garnet-pyroxen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 48 publications
2
100
2
Order By: Relevance
“…Pertermann and Hirschmann (2003) showed that the melt productivity of synthetic pyroxenite G2 in their experiment increased up to 70%/ GPa before the onset of peridotite melting, partly due to heating of the pyroxenite by the enclosing peridotite. These characteristics potentially result in disproportionate contribution of the pyroxenite component to the final erupted melt (Hirschmann and Stolper, 1996;Stracke et al, 1999;Phipps Morgan, 2001;Pertermann and Hirschmann, 2003).…”
Section: Melt Productivitymentioning
confidence: 99%
See 4 more Smart Citations
“…Pertermann and Hirschmann (2003) showed that the melt productivity of synthetic pyroxenite G2 in their experiment increased up to 70%/ GPa before the onset of peridotite melting, partly due to heating of the pyroxenite by the enclosing peridotite. These characteristics potentially result in disproportionate contribution of the pyroxenite component to the final erupted melt (Hirschmann and Stolper, 1996;Stracke et al, 1999;Phipps Morgan, 2001;Pertermann and Hirschmann, 2003).…”
Section: Melt Productivitymentioning
confidence: 99%
“…Pyroxenite, for example, has a larger melt productivity than peridotite, resulting in a higher melting rate (e.g., Hirschmann and Stolper, 1996;Stracke et al, 1999;Pertermann and Hirschmann, 2003;Prytulak and Elliott, 2009) (Section 4.3). The presence of small-scale source heterogeneity, inferred to represent pyroxenitic recycled oceanic crust (Chauvel and Hémond, 2000;Hanan et al, 2000;Skovgaard et al, 2001;Stracke et al, 2003b;Kokfelt et al, 2006;Stracke and Bourdon, 2009) could therefore significantly affect the U-series disequilibria in Icelandic basalts.…”
Section: The Influence Of Source Heterogeneitymentioning
confidence: 99%
See 3 more Smart Citations